Das Hauptgebäude der Universität Hamburg als Gedächtnisort. Mit sieben Porträts in der NS-Zeit vertriebener Wissenschaftlerinnen und Wissenschaftler - Nicolaysen, Rainer (Hamburg University Press, 2011)
The date of May 13, 2011 marked the 100th anniversary of the inauguration of today's main building of the University of Hamburg on Edmund-Siemers-Allee. On the same day, the program begun in 1999 to name its seven lecture halls after outstanding scholars expelled during the Nazi era was completed. This book is therefore being published on these two occasions. In addition to an introduction to the multifaceted history of the building, the volume collects portraits of the seven namesakes of the lecture halls: biographical and werkanalytische approaches to the philosopher Ernst Cassirer, the art historian Erwin Panofsky, the German scholar Agathe Lasch, the mathematician Emil Artin, the lawyer Magdalene Schoch, the international law expert and peace researcher Albrecht Mendelssohn Bartholdy and the social economist Eduard Heimann. Together with the "Stolpersteinen" (Stumbling Stones), which were laid in front of the domed building in 2010, the auditorium appointments form an ensemble through which the main building represents the University of Hamburg in a special way as a central place of remembrance.